1971
DOI: 10.1161/01.cir.43.4.538
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Hemostatic Mechanism After Myocardial Infarction

Abstract: Plasma coagulation factors, adenosine diphosphate-induced platelet aggregation, and fibrinolytic activity were studied in male survivors of myocardial infarction and in healthy normal men. Infarction survivors had significant elevations of factors VIII and X and of adenosine diphosphate-induced platelet aggregation. The fibrinolytic system was altered toward reduced plasminogen activation, increased antiurokinase activity, and elevated antiplasmin activity. These findings suggest that some men with prior myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Changes of blood coagulation, fibrinolysis, platelet number and function have long been recorded in postoperative patients (Dawbarn et al 1928;Payling Wright 1942;Wood et al 1972) but it is uncertain if these changes are more marked or occur more frequently in patients who develop postoperative thrombosis than in patients who do not. Similar changes have also been described after myocardial infarction (Goldenfarb et al 1971). Recently, a few studies have related changes in platelet function, fibrinolytic activity and blood viscosity to the development of postoperative thrombosis detected with 1 25 I-fibrinogen scanning.…”
Section: Blood Testssupporting
confidence: 81%
“…Changes of blood coagulation, fibrinolysis, platelet number and function have long been recorded in postoperative patients (Dawbarn et al 1928;Payling Wright 1942;Wood et al 1972) but it is uncertain if these changes are more marked or occur more frequently in patients who develop postoperative thrombosis than in patients who do not. Similar changes have also been described after myocardial infarction (Goldenfarb et al 1971). Recently, a few studies have related changes in platelet function, fibrinolytic activity and blood viscosity to the development of postoperative thrombosis detected with 1 25 I-fibrinogen scanning.…”
Section: Blood Testssupporting
confidence: 81%
“…R en a u d et al [21] found increase susceptibility to thrombin-induced aggregation among sub jects with suspected coronary artery disease, but normal responses when tested with ADP or collagen. G o ld en fa rb et al [3] found increased ADP-induced platelet aggregation among patients surviving myocardial infarction. Salky and D u g d a le [23] found normal platelet aggregation among patients with ischemic heart disease when tested with ADP, but increased aggregability when tested with collagen.…”
Section: Exercise Testmentioning
confidence: 97%
“…It has been reported that circulating platelet aggregates occur more frequently in patients with transmural myocardial infarction than in patients with subendocardial infarction; 108 ' 274 this is somewhat unexpected because the former condition is more frequently associated with coronary artery thrombosis, and it has been suggested that subendocardial infarction might be asso- 227 Goldenfarbetal. 103 Sano et al 270 Steele et al 304 Salky and Dugdale 267 Frishman et al 97 Yamazaki et al 346 Gormsen et al 104 Zahavi 348 Knudsen et al 162 No 342 Gjesdal 102 Guyton and Willerson 108 Rohrer et al 257 Lowe et al 176 Schwartz et al 274 Amodeo et al 4 Salem et al 264 No ciated with occlusion of the distal coronary vasculature with platelets or platelet-fibrin microthrombi.…”
Section: Referencementioning
confidence: 99%